DECREASING THE HARDNESS Ca, Mg AND HEAVY METALS Fe, Mn, Zn IN RAW WATER WITH ZEOLITE FROM CIKALONG, TASIKMALAYA - Husaini Husaini; Trisna Soenara (Jurnal Zeolit Indonesia, 2006)
The decrease of hardness (Ca, Mg) and heavy metal (Fe, Mn, Zn) contents in raw water was conducted by flowing the sample water through the activated zeolite bed column. Treated water obtained from the experiment obviously met the parameter in standard requirement of drinking water. Activated natural zeolite from Cikalong, Tasikmalaya is able to decrease the content of Ca, Mg, Fe, and Mn in the sample water through the cation exchange process by percolation method with the optimum flow rate of 5 volume bed/hour on the zeolite with the particle size of -10+18 mesh especially for decreasing the hardness (Ca and Mg content). On the other hand, optimum condition for decreasing Fe and Mn contents are reached on the zeolite with the particle size of -10+18 mesh and water flow rate of 10 volume bed/hour. The final treated water contained 0,08 ppm Mn and 0,024 ppm Zn, meanwhile the hardness and other cations have been reduced below the required limit value (0,30 ppm for Fe, 0,10 ppm for Mn, and 0,05 ppm for Zn).